Porous Methyltrimethoxysilane Coated Nanoscale-Hydroxyapatite for Removing Lead Ions from Aqueous Solutions. (16th July 2014) - Ciobanu, C. S.; Iconaru, S. L.; Popa, C. L.; Costescu, A.; Motelica-Heino, M.; Predoi, D.
Abstract : The aim of this study was to synthetize new porous nanoparticles based on methyltrimethoxysilane coated hydroxyapatite (MTHAp) for lead removal form aqueous solutions. The morphological and compositional analysis of MTHAp were investigated by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) equipped with an energy dispersive X-ray spectrometer (EDS). Removal experiments of Pb 2+ ions were carried out in aqueous solutions with controlled concentration of Pb 2+ at a fixed pH value of 3 and 5 respectively. After the removal experiment of Pb 2+ ions from solutions, porous hydroxyapatite nanoparticles were transformed into PbMTHAp_3 and PbMTHAp_5 via the adsorption of Pb 2+ ions followed by a cation exchange reaction. The X-ray diffraction spectra of PbMTHAp_3 and PbMTHAp_5 revealed that the powders, after removal of the Pb 2+ ions, were a mixture of Ca2.5 Pb7.5 (PO4 )6 (OH)2, Pb2 Ca4 (PO4 )2 (SiO4 ), and Ca10 (PO4 )6 (OH)2 . Our results demonstrate that the porous hydroxyapatite nanoparticles can be used as an adsorbent for removing Pb 2+ ions from aqueous solutions.